HEGEMONY ANALYSIS IN AJIDARMA SENO GUMIRA’S PENEMBAK MISTERIUS SHORT STORIES - Rifa'ie, Muhammad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2019)
This study aims to explain the ideological confrontation, the role of intellectual figures, and the formative role text of Penembak Misterius by Seno Gumira Ajidarma uses sociology of literature as the approach of the study with the specialized implementation of hegemony theory by Antonio Gramsci. The results of this study are as follows. First, the ideological confrontation in Penembak Misterius aims at denying the absolute authority of the New Order's formal ideology, namely militarism, development, capitalism, authoritarianism, hedonism, and radicalism. Second, the role of intellectual figures in Penembak Misterius is played to criticize capitalism, materialism, hedonism, developments, national urbanization, also criticizing New Order government officials, the mysterious shooting policy, and at the same time criticizes violence and human rights violations for children. Third, the formative role of the Penembak Misterius text acts as an interrogative text based on the practice of critical memory. It does not only serve as a documentation of historical events but also intends to link the historical events as an emancipation effort.